Discovery of novel 1,3-diaryltriazene sulfonamides as carbonic anhydrase I, II, VII, and IX inhibitors - Suleyman Akocak; Nabih Lolak; Silvia Bua; Claudiu T. Supuran (Taylor & Francis Group, 2018)
A series of new 1,3-diaryltriazene sulfonamides was synthesised by reaction of diazonium salt of metanilamide (3-aminobenzene sulfonamide) with substituted aromatic amines. The obtained new compounds were assayed as inhibitors of four physiologically and pharmacologically relevant human (h) isoforms of carbonic anhydrases (CA, EC 4.2.1.1), specifically, hCA I, hCA II, and hCA VII (cytosolic isoforms), as well as the tumour-associated membrane-bound isoform hCA IX. All isoforms investigated here were inhibited by the newly synthesised 1,3-diaryltriazene sulfonamide derivatives from the micromolar to the nanomolar range. The cytosolic isoforms were inhibited with Kis in the range of 92.3-8371.1 nM (hCA I), 4.3-9194.0 nM (hCA II), and 15.6-9477.8 nM (hCA VII), respectively. For the membrane-bound tumour-associated isoform hCA IX, the KI-s ranged between 50.8 and 9268.5 nM. The structure-activity relationship (SAR) with these newly synthesised metanilamide derivatives are discussed in detail.